2021
DOI: 10.5530/jyp.2021.13.61
|View full text |Cite
|
Sign up to set email alerts
|

Post Covid Multisystem Inflammatory Syndrome with Cervical Lymphadenopathy In A Young Adult

Abstract: Multisystem inflammatory syndrome-children is considered as a paediatric hyper inflammatory condition prompted by severe acute respiratory system coronavirus 2, which has multi-organ involvement. Among them cervical lymphadenopathy is an unusual presentation in multisystem inflammatory syndrome-children. A case study of 17 year old post coronavirus disease 2019 male patient, whose clinical presentation and elevated inflammatory markers on blood tests lead to the diagnosis of multisystem inflammatory syndrome-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…11 Additional case reports and series demonstrated similar findings. 1222 Our case and review of other reported cases strengthens the evidence of association between retropharyngeal inflammation and MIS-C. Absence of an association of retropharyngeal inflammation and MIS-C in the literature might have led to a relatively late diagnosis in some patients such as occurred with our patient.…”
Section: Discussionsupporting
confidence: 81%
“…11 Additional case reports and series demonstrated similar findings. 1222 Our case and review of other reported cases strengthens the evidence of association between retropharyngeal inflammation and MIS-C. Absence of an association of retropharyngeal inflammation and MIS-C in the literature might have led to a relatively late diagnosis in some patients such as occurred with our patient.…”
Section: Discussionsupporting
confidence: 81%